On the males of the orb-weaving spiders Alpaida nigrofrenata (Simon, 1895), A. machala Levi, 1988, and A. cisneros Levi, 1988 (Araneae, Araneidae) and a new synonymy - Poeta, Maria Rita Muniz; Lise, Arno Antonio (Zootaxa, 2015)
The araneid spider genus Alpaida O.P.-Cambridge, 1889 has, until now, 148 described species (WSC 2015). The males of A. nigrofrenata (Simon, 1895), A. machala Levi, 1988, and A. cisneros Levi, 1988 are described here for the first time. A. moka Levi, 1988, based on female specimens, is synonymized with A. xavantina Levi, 1988, based on the study of specimens of both sexes. I.L.F. de Magalhães (MACN) is thanked for reviewing an early revision of this manuscript. We also thank to M. Machado (PUCRS) for the pictures of A. moka, and M. Kolmann (University of Toronto) and A. Londoño Burbano (PUCRS) for review the English. We are grateful to G. Hormiga for helping to improve this manuscript. M.R.M. Poeta was financially supported by CAPES at PPG-Zoo, PUCRS.